QUALITY OF SERVICE. DESCRIPTIVE STUDY OF THE ADMINISTRATIVE SERVICES OF AN ECUADORIAN UNIVERSITY - Hallo Alvear, Fernando; Fajardo, Pamela (mktDESCUBRE; Vol 1 No 3 (2020): Special Edition 1st International Marketing Congress, 2020)
The services offered by the institutions allow the customer to evaluate the quality and also the shopping experience, allowing to measure their satisfaction. This work evaluated the quality of the services of the administrative area of the modality of online studies in an Ecuadorian private university. The methodology used was based on the SERVPERF and SERVQUAL models in the students of the institution, valuing their perceptions and expectations in the five dimensions of the models, for two occasions in the same period in two consecutive years. The results obtained showed that the evaluation of the students was high, regardless of academics. There are also differences in the perception of the quality of services by academic levels in which students are, excluding age, gender or any other variable due to the heterogeneity of the study population.